A study of cascading effect in Southeast Asia and its impact on liner feeder services (Philippines & Vietnam) - Ong, Wan Juin (Nanyang Technological University, 2019)
Cascading effect due to the increasing mega ship sizes has tremendous impact on feeder operators. There is little literature studying the cascading effect, and even more rarely on its impact on feeder operators in SEA. Via looking at ports in Vietnam and Philippines, this report aims to understand how the competition landscape in feeder markets will be altered by competition from MLOs due to the cascading effect. Research is conducted by interviews and secondary data collection. The report focuses on the cascade of vessel from 3,000 TEU to 5,000 TEU. Based on the port data collected, the ports are analysed for their capabilities in handling cascaded ships. Ports are also evaluated based on their cargo volume as employment of ship sizes are justified by volume, thereby identifying ports that may be called directly by MLOs, marginalising the feeder network. Furthermore, SWOT analysis is conducted on feeder operators to identify and recommend strategies. It is key for feeder operators to play on their strength of being a niche market player to capture opportunities such as increase in regional trade. In general, both countries have the capabilities to handle cascaded ships based on port depth, while Vietnam has better prospects of being called on direct service. As such, certain Vietnam ports may develop into regional hub ports. Although feeder from other hub ports, e.g. Singapore, may not be needed, new regional linkages may be developed between Vietnam’s regional hub ports and its feeder ports, thereby benefiting its domestic shipping industry that is well protected by cabotage. Philippines on the other hand, with loosening of cabotage, domestic player may start to face competition from foreign players, negatively affecting the survival of domestic feeder operators. All in all, despite the possible changes in port status, and feeder linkages, feeder operators are still required. It may all be a matter of who is running the service. Every adversity, every failure, every heartache carries with it the seed of an equal or greater benefit, quoted from Napoleon Hill. Although it may be hard times for feeder operators, but if they are willing to change, there might be a bigger opportunity for growth.